Direct Medical Costs of Diabetes and the Foot Ulcer Outpatients in A General Hospital, Yogyakarta - Untari, Eka Kartika; Andayani, Tri Murti; Yasin, Nanang Munif; Asdie, Rizka Humardewayanti (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2025)
Background: In addition to the financial burden that Diabetes Mellitus (DM) places on diabetics and their families due to the complications of Diabetic Foot Ulcers (DFU), treatment costs are escalating. Along with the costs associated with diabetic impairments, direct medical costs may contribute significantly to the financial burden of diabetes.Objectives: This study aimed to determine expenditures associated with DFU, identify cost-influencing factors, and compare the costs of patients with DFU and those without ulcers.Methods: To achieve this objective, this study employed a cross-sectional design and included 198 medical records of DM patients who met the following criteria: age range of 18 to 60 years; type 1 or type 2 DM; receipt of anti-diabetics; payment information; absence of autoimmune or end-stage chronic disease; and absence of corticosteroid. The significance of the cost difference between DFU and non-ulcer patients was evaluated using parametric and non-parametric tests as well as linear regression analysis to determine the cost-influencing factors.Results: This study included 188 patients with type 2 diabetes and ten patients with type 1 diabetes. A total of 131 people with diabetes did not have ulcers, while 67 had a history of DFU. The average direct medical expenses for patients with DFU are IDR 760,146.32, compared to IDR 542,51.24 for patients without ulcer.Conclusion: The presence of ulcers and glycemic conditions had an effect on the direct costs; insulin use also affected the direct costs. The direct costs of diabetic ulcer were significantly higher than non-ulcer, and they were predominantly affected by insulin prescribing.